Gaya Kepemimpinan, Asimetri Informasi dan Ketaatan Aturan Pada Kecurangan Akuntansi: Perilaku Tidak Etis Sebagai Mediasi - Yesi Mutia Basri; Yuhelmi; Rheny Afriana Hanif (Program Studi Akuntansi Fakultas Ekonomi dan Bisnis Universitas Mahasaraswati Denpasar, 2022)
The goal of this study is to see how leadership style, knowledge asymmetry, and regulatory compliance affect accounting fraud, using unethical behavior as a mediating variable. In this study, the Kuansing Regency Government's State Civil Apparatus population was used. ASN served as the sampler for the purpose of purposeful sampling. The information was gathered using a questionnaire that was mailed to the study's participants. The findings of data processing utilizing Warp PLS reveal that Leadership Style and Information Asymmetry have an impact on accounting fraud, but that compliance with accounting rules has no impact. The findings also suggest that unethical behavior mediates the association between accounting fraud and leadership style, information asymmetry, and rule compliance.